The Effect of Nutrition Education with E-Booklet Media on Knowledge and Attitude About Anemia in Adolescent Girls at SMP N 1 Gemuh, Kendal Regency - Anida Nikmah; Johanes Supadi; Yuwono Setiadi (Universitas Teuku Umar, 2022)
Adolescent girls are a group that is susceptible to nutritional problems, one of which is anemia. This is because young women are in a period and have menstruation every month, resulting in iron loss. E-Booklet is one of the educational media that contains text and images that are combined so that it is attractive to the reader. Providing education using e-booklets is expected to increase knowledge and attitudes about anemia so that it can prevent the incidence of anemia in adolescents. This study aims to know the effect of providing nutrition education with e-booklet media on knowledge and attitudes about anemia in adolescent girls at SMP N 1 Gemuh.This study uses a quasi-experimental design with pre and post-test control group design. The data collected are knowledge and attitude score data. Statistical analysis using Independent T-test and Mann Whitney Test.The result showed that the development of an e-booklet on anemia in adolescent girls is worthy to use in research. There was an increase in the average knowledge score, namely in the control group by 22.33 and in the intervention group by 32.6. There was an increase in the average attitude score in the control group which was 0.37 and the intervention group was 0.64. Therefore, Nutrition education with e-booklet media can increase knowledge (p=0.004) and attitudes (p=0.001) about anemia in adolescent girls.